Introduction to Gauss’s Law in Electromagnetism through a Virtual Reality Application - Borges, Luiz Felipe M. R.; Andreão, Rodrigo Varejão; Schimidt, Marcelo Queiroz; Mestria, Mário; Dias, Gilmar S.; Marques, Célio (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Virtual reality (VR) has emerged as a transformative technology in recent years, while Gauss’s law of electromagnetism remains a fundamental principle within Maxwell’s equations. Gauss’s law relates the net electric flux through a closed surface to the charge enclosed within that surface and is particularly useful in scenarios with high symmetry in charge or field configurations. This paper explores the application of Gauss’s law through VR technology to enhance educational outcomes. By providing immersive and interactive experiences, VR enables students to visualize electric fields and flux in three dimensions, interact with closed surfaces, and experiment with dynamic charge configurations. This approach not only strengthens theoretical understanding but also promotes collaborative learning and engagement. Integrating Gauss’s law with VR technology helps bridge the gap between abstract electromagnetic concepts and practical comprehension, making advanced studies in electromagnetism more accessible and engaging. This work focuses on the development of the computational framework, with initial qualitative results from one-semester undergraduate students presented. Quantitative analysis of the impact will be addressed in future research.